2013
DOI: 10.5430/ijelt.v1n1p101
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Speaking and Listening Activities into Teaching Anglo-American Academic Writing Rhetoric

Abstract: In an attempt to widen the range of practical strategies grounded in theoretical speculations of genre theorists, this paper proposes teaching the rhetoric of Anglo-American argumentation through pre-writing listening and speaking activities in ESL academic writing classes. Research shows students' struggles with ESL academic writing include more than inadequate knowledge of vocabulary, grammar, and sentence structure. Instead, the main problem is suggested to be a problem of rhetoric. Students' attachment to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Another research about the effectiveness of mobile language learning applications in teaching vocabulary was explored by researchers Basal, Tanriverdi, and Sari (2016). For four weeks the researchers examined the positive sides of mobile language learning applications on teaching idioms and compared them with traditional and Kanchana and Saha (2015) investigated the benefits of mobile devices in teaching English in India. They discovered that integrating mobile phones into the teaching process can improve the effectiveness of teaching English to learners.…”
Section: Advantages Of Using Mobile Applications In Teachingmentioning
confidence: 99%
“…Another research about the effectiveness of mobile language learning applications in teaching vocabulary was explored by researchers Basal, Tanriverdi, and Sari (2016). For four weeks the researchers examined the positive sides of mobile language learning applications on teaching idioms and compared them with traditional and Kanchana and Saha (2015) investigated the benefits of mobile devices in teaching English in India. They discovered that integrating mobile phones into the teaching process can improve the effectiveness of teaching English to learners.…”
Section: Advantages Of Using Mobile Applications In Teachingmentioning
confidence: 99%
“…Additionally, the mobile devices possess characteristics like portability, functionality, ubiquity, utility and connectivity. It is also discovered that the use of ubiquitous mobile technology (ubiquitous learning) has a positive effect of increasing the idea of innovation and learner involvement, participation and interaction (Huah & Jarrett, 2014;Leone & Leo, 2011). Based on her study, Yunus (2018) reflected that there are various technologies available that is useful and varied to be used in language teaching and learning which currently had become vital to language practice.…”
Section: Technology In Educationmentioning
confidence: 99%
“…In addition, Huah and Jarrett (2014) revealed that the QR code is versatile in terms of generating a guided learning environment and yet still allow learners to immerse in the learning process. This freedom provides learners with the autonomy to navigate learning within their own pace.…”
Section: Technology In Educationmentioning
confidence: 99%
See 1 more Smart Citation